Job-Seeking Stress, Mental Health Problems, and the Role of Perceived Social Support in University Graduates in Korea - Lim, Ah Young; Lee, Seung-Hee; Jeon, Yeongju; Yoo, Rankyung; Jung, Hee-Yeon (Journal of Korean medical science, 2018)
Increases in unemployment and suicide in the young Korean population have recently become major social concerns in the country. The purpose of this study was to examine mental health status in young job seekers and identify sociodemographic factors related to job-seeking stress, depression, and suicidal ideation. We also explored the mediating effect of depression on the relationship between job-seeking stress and suicidal ideation and examined whether social support moderated this effect. In total, 124 university graduates completed the Job-Seeking Stress Scale, Beck Depression Inventory-II, Beck Scale for Suicide Ideation, and Multidimensional Scale of Perceived Social Support. Descriptive statistics were calculated for participants' general characteristics, and t-tests or analyses of variance, correlation analysis, simple mediation analysis, and mediated moderation analysis were performed. Of the 124 participants, 39.5% and 15.3% exhibited clinical levels of depression and suicidal ideation, respectively. Sociodemographic factors (i.e., sex, academic major, educational expenses loan, and willingness to accept irregular employment) were associated with job-seeking stress, depression, and suicidal ideation. Women and graduates who were willing to accept irregular employment exhibited high levels of job-seeking stress, depression, and suicidal ideation. Job-seeking stress affected suicidal ideation via depression, and perceived social support moderated the effect of job-seeking stress on depression and the effect of depression on suicidal ideation. The results suggest that depression management and interventions are urgently required for young job seekers, and social support should be provided to assist them both emotionally and economically.